Relationship between the chlorophyll a fluorescence and the yield in banana (Musa AAA Simmonds cv. Cavendish) - Feria-Gómez, Diego Felipe; Londoño-Puerta, Diego Alejandro; Córdoba-Gaona, Oscar de Jesús (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Chlorophyll fluorescence is used to characterize the plant response to natural environments or under stress conditions. This study aimed to identify correlations between the maximum quantum efficiency of PSII (Qy) with climatic and soil variables associated with bunch weight. The experimental design used in the field corresponds to an observational and longitudinal study, where 72 production units in the independent vegetative stage were randomly selected, of which 36 units from a low production area and 36 from a high production area. In each unit, the quantum yield (Qy: Fv/Fm) was measured and correlated with climatic and soil variables, the nutrient content in the leaves, and the average weight of the cluster in each sampled batches. The results indicated a correlation between Qy of -0.703 concerning temperature and -0.583 with radiation. On the other hand, pH and resistance to soil penetration are directly related to Qy to a lesser extent, with r2 values of 12.77 and 24.28%, respectively. Precipitation, wind, gusts, dew point, atmospheric pressure, and texture composition of the soil do not significantly affect Qy variation; when attacks of leaf pests (mites) occur, significant reductions are also observed in this. Qy is a variable that responds to the stress generated by factors external to the plant, these can significantly affect production, and which is reduced by up to two kg per cluster, with a bias of three to four weeks, when the loss of 0.04 points in the value of Qy occurs.